Analisis Kinerja Keuangan Perusahaan Hanjaya Mandala Sampoerna Tbk Ditinjau Dari Rasio Likuiditas, Solvabilitas, Profitabilitas, Aktivitas Pada Tahun 2018-2022 - Nurmala Putri Fatimah; Indah Listyani; Ahmad Idris (Lembaga Pengembangan Kinerja Dosen, 2024)
In this study, researchers want to see the financial performance condition of the Hanjaya Mandala Sampoerna company when measured using liquidity, solvency, profitability and activity ratios. The Hanjaya Mandala Sampoerna Company is the largest tobacco cigarette industry in Indonesia. The data used for the ratio measurement process are taken from the company's financial reports on the Indonesia Stock Exchange Investment Gallery website using documentation and library data collection techniques (Library Research), namely collecting and combining several data that are appropriate to research. This type of research is descriptive quantitative which describes several phenomena which are then described and analyzed again. The results of research over the last five years of Hanjaya Mandala Sampoerna Tbk's financial performance on liquidity, solvency and profitability ratios are still said to be not good, but the activity ratio produces good financial performance in 2018-2022.